In vivo membrane assembly of split variants of the E.coli outer membrane protein OmpA. - Koebnik, R (1996)
The two-domain, 325 residue outer membrane protein OmpA of Escherichia coli is a well-established model for the study of membrane assembly. The N-terminal domain, consisting of approximately 170 amino acid residues, is embedded in the membrane, presumably in the form of a beta-barrel consisting of eight antiparallel transmembrane beta-strands. A set of 16 gene variants carrying deletions in the membrane-embedded domain of OmpA was constructed. When pairs of these mutant genes were co-expressed in E.coli, it was found that a functional OmpA protein could be assembled efficiently from two complementary protein fragments. Assembly was found when the polypeptide chain was split at the second or third periplasmic turn. All four protein termini were located in the periplasmic space. Interestingly, duplication of transmembrane strands five and six led to a variant with an unusual topology: the N-terminus of one fragment and the C-terminus of the other fragment were exposed at the cell surface. This is the first demonstration of correct membrane assembly of split beta-structured membrane proteins. These findings are important for a better understanding of their folding/assembly pathway and may have implications for the development of artificial outer membrane proteins and for the cell surface display of heterologous peptides or proteins.